Executive EQ - Cooper, Robert K. (Grosset/Putnam, 1997)
In recent years there has been a number of research studies and management reports showing connections between various competencies of emotional intelligence and bottom-line business results. These include significant gains in revenue, productivity, innovation, teamwork and profitability. Cost savings, reduced cycle time, greater market share, and increased trust, loyalty and commitment from co-workers, employees, customers and clients are further proven benefits. Many people are beginning to realize that simply being blessed with a high IQ does not guarantee a path to career success. Emotional Intelligence, or EQ, is equally, perhaps even more important. Knowing one's own emotions and controlling them, recognizing and understanding emotions in others and self-motivation are the key dimensions of EQ. This practical book aims to show you how to develop and apply EQ in your workplace. It includes an EQ map for self-assessment